2006
DOI: 10.1592/phco.26.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Drug Adherence and Blood Pressure Control in Patients with Hypertension

Abstract: Age, sex, race and depression are associated with antihypertensive drug adherence and blood pressure control. Self-reported and refill adherences appear to provide complementary information and are associated with reductions in systolic and diastolic blood pressure of similar magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
106
3
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 53 publications
(41 reference statements)
16
106
3
2
Order By: Relevance
“…2,3 Socioeconomic factors, such as income, education and ethnicity, have been extensively investigated as possibly associated with the rate of treatment and control of hypertension. [4][5][6][7][8][9] However, data on this issue mainly reflect private, or mixed publicprivate, health care systems. Despite the fact that the Italian National Health Service (NHS) provides universal coverage for health care, including drug treatment for hypertension, socioeconomic disparities in the occurrence of coronary heart disease still persist.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Socioeconomic factors, such as income, education and ethnicity, have been extensively investigated as possibly associated with the rate of treatment and control of hypertension. [4][5][6][7][8][9] However, data on this issue mainly reflect private, or mixed publicprivate, health care systems. Despite the fact that the Italian National Health Service (NHS) provides universal coverage for health care, including drug treatment for hypertension, socioeconomic disparities in the occurrence of coronary heart disease still persist.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Comorbid conditions, notably depression, may also impact on a patient's ability to adhere and persist with antihypertensive treatment. 36 The relationships between health-care professionals and the patient are crucial to overcoming patient-related barriers to blood pressure control. Management styles that are autocratic or lack meaningful interaction with the patient are unlikely to deliver acceptable goal rates.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed similar antihypertensive medication adherence between cancer survivors and the comparison group (84.0% vs. 85.6%) using the claim data set. 17 The agreement between selfreported adherence and refill adherence is reported to be only poor to fair, 9,22 and it has been suggested that these two methods reflect different dimensions of medication-taking behavior. 34 Other potential explanations would be increased awareness of non-cancer care among cancer survivors between the study period (2002 vs. 2009), 35,36 and insufficient adjustment of potential confounders, such as education, employment status and smoking, in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] According to the Health Belief Model, certain behavioral factors, such as perceived risk for the disease and perceived benefit of treatment, [10][11][12] could also affect the management of hypertension. Unlike hypertensive patients without cancer, cancer survivors with hypertension are more likely to consider cancer recurrence, metastasis and a second primary cancer as major health concerns, and usually require more complex care.…”
Section: Introductionmentioning
confidence: 99%